Geometric Design and Outcome of Transposition Flaps for Scalp Reconstruction (Journal of Rangpur Medical College, 2022)
Background: The scalp is a unique part of the human body and various etiological factors, such as tumor extirpation, avulsion, infection, burns, or trauma, can lead to scalp defects. Primary closure, skin grafting, local flaps, tissue expansion or free tissue transfer is modalities available for scalp reconstruction. Local flap coverage is best option for full thickness loss with exposed bone. Among various local flap transposition flap is reasonable and flexible option with good outcome for scalp reconstruction.Objective: The purpose of this study was to evaluate the geometric design of transposition flap for scalp reconstruction concerning the dimension of the defect and outcome the surgery.Methods: This was a prospective observational study, conducted in the Burn & Plastic Surgery department of Rangpur medical college hospital, Rangpur and different private hospitals of Rangpur city over a period of three years from June 2018 to July 2021 through purposive sampling. All aged patients having single full thickness scalp wound with loss of pericranium were included in this study. In all cases transposition flaps were used. All the flaps were elevated through sub galeal lose areolar plane. Flap donor site was covered with split thickness skin graft taken from thigh. Surgical technique, patient factors and outcome were evaluated.Results: A total 50 patients were operated. The age range was 07-68 years, among them 36% patient were in the age range of 21 – 30 years. 80% patients in this series were male. In this series 64 % patients were construction and electric worker by profession. Electric burn was the main (64%) cause of soft tissue defect of scalp. The majority (46%) of the patients had a wound dimension of 51-70 cm2, smallest was (5x6) = 30cm2 and largest was (9x15) = 135cm2, indicating that extent of soft tissue defects in this series is quite extensive. 12 (24%) patients had complication and all were due to infection, seven patients had infection in flap recipient site, 2 patients had infection in flap donor site and 3 patients developed infection in skin donor site. There was no flap loss in our study.Conclusion: Sound knowledge of flap geometry and clear evaluation of the defect is mandatory for successful reconstruction of scalp defect. A local transposition flap with donor site skin grafting is reliable option for reconstruction of full thickness scalp defect in most instances.J Rang Med Col. September 2022; Vol. 7, No. 2:52-57